2008
DOI: 10.1016/j.nonrwa.2007.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Impurity bands and quasi-Bloch waves for a one-dimensional model of modulated crystal

Abstract: This paper investigates a simple one-dimensional model of incommensurate "harmonic crystal" in terms of the spectrum of the corresponding Schrödinger equation. Two angles of attack are studied: the first exploits techniques borrowed from the theory of quasi-periodic functions while the second relies on periodicity properties in a higher-dimensional space. It is shown that both approaches lead to essentially the same results; that is, the lower spectrum is splitted between "Cantor-like zones" and "impurity band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…The new bands look like being k-periodic hence the original Brillouin zone is now too narrow to include them; see also [11] for a similar observation with a different type of perturbation. In [11], we observed that impurity bands appear to be parabolic: a plausible interpretation is that electrons perceive somehow the average of the corresponding very oscillating potential (like the so-called Jellium metal model [6]) and thus display a parabolic dispersion relation. The effect of the disordered medium boils down to the effective mass only.…”
Section: Strong Disorder: K-periodic Impurity Bands Formentioning
confidence: 76%
See 2 more Smart Citations
“…The new bands look like being k-periodic hence the original Brillouin zone is now too narrow to include them; see also [11] for a similar observation with a different type of perturbation. In [11], we observed that impurity bands appear to be parabolic: a plausible interpretation is that electrons perceive somehow the average of the corresponding very oscillating potential (like the so-called Jellium metal model [6]) and thus display a parabolic dispersion relation. The effect of the disordered medium boils down to the effective mass only.…”
Section: Strong Disorder: K-periodic Impurity Bands Formentioning
confidence: 76%
“…It looks also like a smooth process as has been shown in [2] using the concepts of "resonance tongues" and "instability pockets". The upper part of the spectrum is rather messy, so we didn't display it; see however [11].…”
Section: Weak Disorder: Cantor Spectrum For Various Values Of εmentioning
confidence: 96%
See 1 more Smart Citation
“…This governs the quantum wave function of an independent electron within a crystalline lattice perturbed by some impurities whose dissemination induces long-range order only, which is rendered by means of the quasi-periodic potential q. In the paper [21], a simple onedimensional model of an incommensurable "harmonic crystal" is studied in terms of the spectrum of the corresponding Schrödinger equation.…”
Section: Applicationsmentioning
confidence: 99%
“…This numerical evidence leads to the conjecture that the wavefunction (and other quantities related to it) might not be continuous functions of the parameter α. Related work has also been presented in [6,7]. In the context of free-electron lasers (which are periodic systems), related work has been presented in [8].…”
Section: Introductionmentioning
confidence: 99%